2020
DOI: 10.3390/pathogens9010058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hypoxia-Inducible Factor-1 Alpha (HIF-1α) in Equine Sarcoid: An Immunohistochemical and Biochemical Study

Abstract: Background: equine sarcoids are the most frequent skin tumors in equidae worldwide. It is well known that delta bovine papillomaviruses are their causative agents. We have recently shown the presence in equine sarcoids of abnormal vessel structures, which could cause a hypoxic condition. The aim of this study was to analyze the expression of hypoxia-inducible factor-1 alpha (HIF-1α) in a subset of BPV positive equine sarcoids and explore the relationship with vascular endothelial growth factor (VEGF) expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 73 publications
(109 reference statements)
1
9
0
Order By: Relevance
“…This is why we aimed at establishing a hypoxia-induced control for the immunofluorescent experiments. To our knowledge, this is not described for equine cultures to date even though there are reports on mainly intracytoplasmic HIF-1α expression in other equine tissues [ 37 , 38 ] and sarcoids as well as keratinocyte cultures [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is why we aimed at establishing a hypoxia-induced control for the immunofluorescent experiments. To our knowledge, this is not described for equine cultures to date even though there are reports on mainly intracytoplasmic HIF-1α expression in other equine tissues [ 37 , 38 ] and sarcoids as well as keratinocyte cultures [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Martano et al 50 have observed an increase of HIF‐1α expression in equine sarcoids; this mediator plays a key role in oxygen homeostasis 51 . Available literature confirms that VEGF expression is mediated by HIF‐1α during hypoxia, and the expression of HIF‐1α directly correlates with VEGF expression and tumour vascularity in several tumour types 50 . Based on these results, it has been hypothesised that BPV could have a relevant role in HIF‐1α pathway regulation, contributing to the development of equine sarcoids by promoting HIF‐1α/VEGF‐mediated tumour angiogenesis 50 …”
Section: Changes In Gene Expression In Equine Sarcoid Tissuementioning
confidence: 99%
“…As a consequence, in equine sarcoids, VEGF may be involved not only in angiogenesis, but also in ECM homeostasis maintenance and remodelling 24 . Furthermore, Martano et al 50 have observed an increase of HIF‐1α expression in equine sarcoids; this mediator plays a key role in oxygen homeostasis 51 . Available literature confirms that VEGF expression is mediated by HIF‐1α during hypoxia, and the expression of HIF‐1α directly correlates with VEGF expression and tumour vascularity in several tumour types 50 .…”
Section: Changes In Gene Expression In Equine Sarcoid Tissuementioning
confidence: 99%
“…95 On the other hand, the development of equine sarcoid is associated with an elevated level of the transcription factor hypoxia-inducible factor-1 alpha (HIF-1α). 64 This transcription factor is activated in response to hypoxia and leads to angiogenesis, the development of new vessels necessary for neoplastic invasion, growth, and metastasis.…”
Section: Molecular Featuresmentioning
confidence: 99%